Unexpected behavior of irradiated spider silk links conformational freedom to mechanical performance1. Issue 24 (28th June 2015) - Perea, G. Belén; Solanas, Concepción; Plaza, Gustavo R.; Guinea, Gustavo V.; Jorge, Inmaculada; Vázquez, Jesús; Pérez Mateos, Jorge M.; Marí-Buyé, Núria; Elices, Manuel; Pérez-Rigueiro, José
<x xml:space="preserve">Abstract</x> Despite the modification of the molecular weight of the protein chains, UV irradiation does not exert any effect on the compliance of maximum supercontracted major ampullate gland silk fibers.